Enhancing Postharvest Quality of Cavendish Bananas (Musa acuminata) with Lactobacillus sp. - Hernando, Denrel T. (Department of Agronomy and Horticulture, IPB University, 2025)
Cavendish bananas are among the most widely cultivated and consumed varieties worldwide, valued for their sweetness, texture, and versatility. However, postharvest diseases, particularly crown rot caused by Fusarium and Colletotrichum spp., present significant challenges, resulting in substantial losses in both quality and yield. Traditional management relies on synthetic chemicals, such as prochloraz and calcium hypochlorite; however, concerns over pesticide residues, environmental impact, and consumer preference for low-chemical produce have driven the search for safer alternatives. Lactic acid bacteria, particularly Lactobacillus sp., have shown promise in agriculture due to their ability to produce organic acids, such as lactic acid, which suppress pathogens and enhance fruit quality. This study investigated the efficacy of Lactobacillus sp. as a postharvest treatment for Cavendish bananas, comparing it with conventional chemical treatments. The main objectives were to evaluate fruit quality, crown rot incidence, sensory attributes, and economic viability. Results demonstrated that bananas treated with Lactobacillus sp. (10 ml.L-1 water) achieved a high select quality (SQ) rating of 94.25%, closely comparable to 94.65% observed in synthetic chemical-treated fruits. Untreated bananas and those treated with calcium hypochlorite exhibited lower quality and a higher incidence of crown rot. Sensory evaluation revealed no significant differences in odor, aroma, flavor, texture, or overall acceptability across treatments, indicating that Lactobacillus sp. does not compromise sensory qualities. Economic analysis further highlighted the benefits of this biological treatment, with Lactobacillus sp. yielding the highest return on investment (61.7%), outperforming synthetic chemicals at 37.5% ROI. These findings highlight Lactobacillus sp. as a cost-effective and sustainable alternative to traditional fungicides, offering comparable fruit quality and profitability while reducing chemical reliance. This approach aligns with consumer demand for low-chemical produce, particularly in markets such as Japan, and supports environmentally sustainable postharvest disease management.